OS SENTIDOS DO FUTEBOL ESPETÁCULO PARA ESTUDANTES DE DISTINTAS CLASSES SOCIAIS - Toto, Rogério (2007)
The present study tries to identify how the belonging of the social class interferes in the directions and perspectives of a Brazilian young person related to the soccer show, as well the understanding of the social mechanisms which determine the decision of the subjects to invest in the professional sport career instead of a school long trajectory. We begin with some social approach to the critical analysis of the processes of diffusion, popularization and professional development occurred in the context of the post-industrial society. We emphasize the conflictive change of the modality, at the beginning practiced by the high class with social-distinctive reasons for sport of mass ideal of social increasing of the popular class, besides the dependence with the media, of the reasons which took it to characterize itself as a product of the cultural industry, concluding in the change of the soccer into goods submitted to laws and logic of the society of consume. Next, we joined the relations of power, alliance and competition of the social agents which participate of the complex field of the sports practice with the sources that the young public establish contact with the sport show, in this aspect, special attention was given to the media, diffuser of the ideology of an open capitalist society , which reinforce the idea of the sport to be a way of social increasing for people of low income, at the same time that it omits in its discourse the real probabilities of fulfillment of the sporting success. The field research was fulfilled in two schools of São Bernardo do Campo city SP, one of them from the public schools and the other from the private ones. This way, we established two groups with students from different social classes, composed of students from the first grade of the high school, male sex, with 15 years old, and soccer trainers in the Physical Education classes. We used the method of the participative watching and the interviews as instruments for the collection of data, and we joined it to the objectives of the study, we structured the analysis of the collected material in six categories, including questions about: the continuation of the study and work, the tendencies to the professional sporting practice, the social representation around the soccer, the use and habits in the spare time, and the expectations of the sportive practice influenced by the familiar cultural heritage. As theoretical reference of analysis, we used Pierre Bourdieu the concepts of field, habitus, strategy, economic and social capital, and mainly cultural capital, beginning from the hypothesis that the cultural level of the student and his family is a factor that interferes in the directions and ways of appropriation of the sport. Among other conclusions, we got as a result the configuration of a professional sporting trajectory for the students of low social class, in opposite of the long school trajectory strategically adopted by the students of the high social class.(AU)